Basic Flight Mechanics A Simple Approach Without Equations - Tewari, Ashish (Springer International Publishing : Imprint: Springer, 2016)
This book presents flight mechanics of aircraft, spacecraft, and rockets to technical and non-technical readers in simple terms and based purely on physical principles. Adapting an accessible and lucid writing style, the book retains the scientific authority and conceptual substance of an engineering textbook without requiring a background in physics or engineering mathematics. Professor Tewari explains relevant physical principles of flight by straightforward examples and meticulous diagrams and figures. Important aspects of both atmospheric and space flight mechanics are covered, including performance, stability and control, aeroelasticity, orbital mechanics, and altitude control. The book describes airplanes, gliders, rotary wing and flapping wing flight vehicles, rockets, and spacecraft and visualizes the essential principles using detailed illustration. It is an ideal resource for managers and technicians in the aerospace industry without engineering degrees, pilots, and anyone interested in the mechanics of flight. Provides readers with a thorough understanding of the physical principles behind flight mechanics without the need of complicated mathematics; Encompasses all types of flight covered in one book from the biomechanics of birds to airplanes and rockets; Illustrates key properties of flight with many schematic diagrams and examples to highlight important principles; Includes appendices on atmospheric properties as well as basic flight equations for more mathematically inclined readers.